Road Transport of Dangerous Goods in Poland – Risk Analysis - Monika Madej; Michał Pająk (Promet - Traffic&Transportation, 2019)
The paper presents the methodology for the risk analysis of the road transport of dangerous goods. The risk analysis includes the societal risk for communities living or staying within a radius of six kilometres from all national roads in Poland. The GIS software was employed to make this analysis. The prepared matrix has included the product of the likelihood of a road accident involving explosive dangerous goods and the consequences for communities living in the abovementioned area. The likelihood analysis was developed for explosive and toxic dangerous goods. The consequence analysis was based on the population density, according to which a respective number of people was assigned to each building, depending on the time of day (daytime, nighttime). Each stage of the analysis was presented in the form of a map. In total, two variants of the likelihood analysis, four variants of the consequence analysis and four variants of risk analysis have been developed. All analyses have been developed for the entire country.